2008
DOI: 10.1007/s00436-008-1178-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence between island and continental populations of the parasitic nematode Labiosimplex australis in Australia

Abstract: Sequences of the first and second internal transcribed spacers (ITS-1 and ITS-2) of nuclear ribosomal (r) DNA were characterised for Labiosimplex australis, a parasitic nematode of macropodid marsupials from continental Australia and from island populations which have been isolated from mainland Australia for relatively short periods of time (<40,000 years). The results showed that the geographically isolated populations of L. australis on Kangaroo Island and Tasmania were genetically different from each other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…‘Sea level’ is supposed to produce different pressures on natural selection that forces colonization toward higher altitude. Populations located at different elevations were motivated by different levels of potential adaptation to the local environment [41,42], leading to the occurrence of loci diverging. Limited by the number of the populations and the size of the populations plus due to some types of bottleneck events [43], expansion of the populations upon one species was not always observed.…”
Section: Discussionmentioning
confidence: 99%
“…‘Sea level’ is supposed to produce different pressures on natural selection that forces colonization toward higher altitude. Populations located at different elevations were motivated by different levels of potential adaptation to the local environment [41,42], leading to the occurrence of loci diverging. Limited by the number of the populations and the size of the populations plus due to some types of bottleneck events [43], expansion of the populations upon one species was not always observed.…”
Section: Discussionmentioning
confidence: 99%
“…The first and second internal transcribed spacers (ITS1 and ITS2) are comparatively more variable than the rRNA coding regions and have thus been used for differentiation of closely related species (1,4,6,10,22,23). We PCR amplified and sequenced ITS1 from A. costaricensis (two laboratory strains from Costa Rica and Brazil), A. vasorum (from naturally infected hosts in United Kingdom), and A. cantonensis from three geographical regions (one laboratory strain from Japan plus nine environmental isolates from Hawaii and New Orleans, LA) to assess the variability of this potential PCR target.…”
mentioning
confidence: 99%
“…ITS-1 and ITS-2) known to allow the specific identification of strongylid nematodes of macropodids and other vertebrates [16][17][18][19][20][21]. The low degree of nucleotide variation (r0.2%) detected in the ITS-1 region within G. trifidospicularis from five host species and 13 geographical locations was less than the levels of intraspecific variation (usually r1%) detected for a wide range of strongylid nematodes [18,19,[22][23][24][25][26][27], including those of the superfamily Trichostrongyloidea, to which the genus Globocephaloides belongs [28]. The sequence homogeneity in ITS rDNA within G. trifidospicularis contrasts with previous MEE results, showing a fixed allelic difference of 17% between (pooled) samples of G. trifidospicularis from sympatric hosts in Tasmania [7], and does not support a previous proposal that G. trifidospicularis represents a complex of at least two species.…”
mentioning
confidence: 81%
“…There is a clear precedent for cryptic species in strongylid nematodes of macropodid marsupials. A number of previous studies have discovered cryptic species and/or proposed adaptive speciation [13,23,24,[30][31][32][33]. For example, Huby-Chilton et al [31] used a mutation scanning-sequencing approach to detect 5.2% sequence variation in ITS-2 between two forms of Zoniolaimus mawsonae (Nematoda: Strongyloidea) from M. rufus and concluded that they represented sibling species.…”
mentioning
confidence: 97%